The Digital Economy in Latin American Foreign Trade: Post-Pandemic Challenges for Sustainable Development - Henry Bernardo Garay Canales; Santiago Alberto Casas Luna; Candi Pastora Malaga Davila; Juan Manuel Aponte Cajavilca; Dominga Micaela Cano Ccoa; Manuel Eduardo Vilca Tantapoma; Gilbert Roland Alvarado Arbildo; Herlinda Melissa Aguirre López (Qubahan Academic Journal)
This article examines the digital transformation in Latin America's foreign trade and points out the emerging challenges and opportunities in the post-pandemic context of COVID-19. Digitalization has redefined trade structures and international trade dynamics, driving the growth of e-commerce and the modernization of customs processes. However, the region faces significant disparities in infrastructure, regulatory frameworks, and technological capabilities, which affect its global competitiveness. Through a detailed analysis of progress and obstacles between 2018 and 2023, this study identifies gaps and opportunities to strengthen digital integration and promote sustainable development. Data from official sources such as ECLAC and case studies of Latin American countries are used to assess the adoption of digital technologies in foreign trade. The results reveal that, although digitization has facilitated cross-border trade and improved operational efficiency, important challenges persist in cybersecurity, digital divides, and adaptation of public policies. This article makes an important contribution by offering a comprehensive view of how the digital economy is reshaping foreign trade in Latin America and provides valuable information for academics, policymakers, and private sector actors interested in the region's sustainable development and international competitiveness.